THE EFFECT OF PICTURE-CUED TASK ON STUDENTS’ WRITING SKILL IN RECOUNT TEXT AT THE TENTH GRADE OF SMA SWASTA GAJAH MADA MEDAN - Lidia Apriani Daeli; Fenty Debora Napitupulu; Carolina Pakpahan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of using the Picture-Cued Task on students’ writing skills in recount texts. Students often experienced difficulties in generating ideas, organizing events chronologically, and using appropriate vocabulary and grammar. This study employed a quantitative approach with a quasi-experimental design, specifically the nonequivalent control group design. The population consisted of all tenth-grade students, while the sample consisted of two classes: 20 students in the experimental class and 20 students in the control class. The data were collected through pre-test and post-test writing assessments and were analyzed using an analytic scoring rubric. The findings showed that the mean score of the experimental class increased from 62.05 in the pre-test to 83.25 in the post-test, while the mean score of the control class increased from 61.05 to 79.05. The result of the t-test showed that the t-observed value (4.15) was higher than the t-table value (2.024) at the significance level of 0.05. Therefore, the alternative hypothesis (Hₐ) was accepted and the null hypothesis (H₀) was rejected. It can be concluded that the Picture-Cued Task had a significant effect on improving students’ writing skills in recount texts because it helped students generate ideas, organize events, and express their experiences more clearly.